The Effectiviness of Dysmenorrhea Gymnastics as an Alternative Therapy in Reducing Menstrual Pain - Mei Lina Fitri Kumalasari (State Islamic University of Sunan Ampel, 2017)
Menstrual pain occurs due to the imbalance of the hormones which will cause the uterine muscles to contract and lead to colic pain. Approximately 50 % of women worldwide and 90 % of Indonesian women suffer from menstrual pain. Pharmacological therapy is the most popular treatment used to relieve menstrual pain. Unfortunately, it leads to indisputable side effects on health. Therefore, safety alternative treatments such as dysmenorrhea gymnastics are signifficantly needed to improve bloodstream in the uterus and produce endorphins which can relieve menstrual pain. The aim of the study wasto determine the effectiveness of dysmenorrhea gymnastics to relieve the level of menstrual pain. The method of study is systematic review on 14 studies of the efectiveness of exercise dysmenorrhea gymnastics to relieve menstrual pain. The results obtained are dysmenorrhea gymnastcs can relieve menstrual pain with a mean value of 4.006. Conclusion: dysmenorrhea gymnastics can relieve menstrual pain and better done in the afternoon.